Social instability stress differentially affects amygdalar neuron adaptations and memory performance in adolescent and adult rats - Tsai, Sheng-Feng; Huang, Tung-Yi; Chang, Chia-Yuan; Hsu, Yuan-Chang; Chen, Shean-Jen; Yu, Lung; Kuo, Yu-Min; Jen, Chauying J. (Frontiers in Behavioral Neuroscience, 2014)
Adolescence is a time of developmental changes and reorganization in the brain. It has been hypothesized that stress has a greater neurological impact on adolescents than on adults. However, scientific evidence in support of this hypothesis is still limited. We treated adolescent (4-week-old) and adult (8-week-old) rats with social instability stress for five weeks and compared the subsequent structural and functional changes to amygdala neurons. In the stress-free control condition, the adolescent group showed higher fear-potentiated startle responses, larger dendritic arborization, more proximal dendritic spine distribution and lower levels of truncated TrkB than the adult rats. Social instability stress exerted opposite effects on fear-potentiated startle responses in these two groups, i.e., the stress period appeared to hamper the performance in adolescents but improved it in adult rats. Furthermore, whilst the chronic social stress applied to adolescent rats reduced their dendritic field and spine density in basal and lateral amygdala neurons, the opposite stress effects on neuron morphology were observed in the adult rats. Moreover, stress in adolescence suppressed the amygdala expression of synaptic proteins, i.e., full-length TrkB and SNAP-25, whereas, in the adult rats, chronic stress enhanced full-length and truncated TrkB expressions in the amygdala. In summary, chronic social instability stress hinders amygdala neuron development in the adolescent brain, while mature neurons in the amygdala are capable of adapting to the stress. The stress induced age-dependent effects on the fear-potentiated memory may occur by altering the BDNF-TrkB signaling and neuroplasticity in the amygdala.